HUBUNGAN KECEPATAN TERHADAP KETERAMPILAN DRIBBLING DALAM PERMAINAN SEPAK BOLA DI SSB BHIRAWA TIRTOYUDO: HUBUNGAN KECEPATAN TERHADAP KETERAMPILAN DRIBBLING DALAM PERMAINAN SEPAK BOLA DI SSB BHIRAWA TIRTOYUDO - Muhammad Ilham Amin; Winarno, Winarno; Kurniawan, Rubi; Hartati, Tri Asih Wahyu; Pradipta, Anangga Widya; Lutfiansyah, Muhammad Noufal (Universitas Hamzanwadi, 2025)
This study was motivated by the importance of understanding the relationship between physical condition and technical skills in early age soccer. The problem raised was the lack of clarity regarding the direct relationship between running speed and dribbling skills in young players at SSB Bhirawa Tirtoyudo. The purpose of this study was to analyze the significant relationship between speed and soccer dribbling skills. The method used was quantitative correlational with a sample of 35 players selected purposively. The research instruments were a 30-meter running speed test and a standardized zig-zag dribbling test. The data were analyzed using Pearson's correlation test after fulfilling the assumptions of normality and linearity. The results showed a strong and significant negative relationship between speed and dribbling skills (r = -0.726, p < 0.001). The coefficient of determination (R²) of 0.527 indicated that 52.7% of the variation in dribbling skills was influenced by speed. The conclusion of this study is that speed is a determining factor that greatly contributes to dribbling quality. Implicitly, coaches are advised to integrate speed training into dribbling skill development programs to optimize the holistic performance of young players.